If it's not what You are looking for type in the equation solver your own equation and let us solve it.
d in (-oo:+oo)
3*(4-(2*d)) = -12 // + 12
3*(4-(2*d))+12 = 0
3*(4-2*d)+12 = 0
3*(4-2*d)+12 = 0
24-6*d = 0
24-6*d = 0
24-6*d = 0 // - 24
-6*d = -24 // : -6
d = -24/(-6)
d = 4
d = 4
| 6(-10-3m)=12 | | 6(4+4b)=-24 | | 4(-5t+3)=-8 | | 5(2m-2)=50 | | 5(-2m+4)=-20 | | 3(8+7w)=87 | | 3(1n-9)=-54 | | 5(5+4k)=25 | | 3(6-3t)=117 | | 5(-4-2m)=-110 | | 4(-7b+2)=204 | | 7(-3m+5)=77 | | 4(6k+1)=220 | | 7(4b+4)=-252 | | 2(4-5b)=-102 | | 2(7b+3)=34 | | 7(3k-1)=35 | | 4(7d+6)=80 | | 6(5d-1)=144 | | 5(-6t+4)=-220 | | 2(-3n-9)=-36 | | 7(-5t+9)=28 | | 5(1a-8)=5 | | 6(-9+d)=-84 | | 2(-1d+5)=6 | | 5(10-2m)=50 | | 6(6+2t)=132 | | 6(-1+1n)=36 | | 7(6-6d)=420 | | 5(5+6d)=205 | | 2(6d+9)=138 | | 4(-3w+9)=-48 |